2006
DOI: 10.1248/bpb.29.2419
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Oxyresveratrol from Smilacis Chinae Rhizome on Amyloid .BETA. Protein (25-35)-Induced Neurotoxicity in Cultured Rat Cortical Neurons

Abstract: We previously reported that] c , and then by inhibiting glutamate release and ROS generation. Furthermore, these effects of oxyresveratrol may be associated with the neuroprotective effect of Smilacis chinae rhizome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…The Ethical Committee of Ataturk University approved the study protocol (B.30.2.ATA.0.23.85-73). Primary rat cerebral cortex neuron cultures were prepared using rat foetuses as described previously (Ban et al 2006). Briefly, a total of nine new-born Sprague-Dawley rats were used in the study.…”
Section: Healthy Neuron Cell Culturesmentioning
confidence: 99%
“…The Ethical Committee of Ataturk University approved the study protocol (B.30.2.ATA.0.23.85-73). Primary rat cerebral cortex neuron cultures were prepared using rat foetuses as described previously (Ban et al 2006). Briefly, a total of nine new-born Sprague-Dawley rats were used in the study.…”
Section: Healthy Neuron Cell Culturesmentioning
confidence: 99%
“…15 Moreover, we have demonstrated that the suppression of intracellular [Ca 2+ ] i elevation by numerous antioxidants such as oxyresveratrol, gallic acid, catechin, and epicatechin is primarily responsible for the ability of these compounds to prevent Ab (25-35)-induced neuronal death. 26,[38][39][40] Therefore, results from the present study suggested that the antidementia effect of I. latifolia might be attributable to the prevention of apoptosis by suppressing intracellular [Ca 2+ ] i increases and ROS generation due to the antioxidant components of this plant.…”
Section: Discussionmentioning
confidence: 58%
“…Primary rat cerebral cortex neuron cultures were prepared using rat foetuses as described previously (Ban et al 2006). Briefly, a total of nine new-born Sprague-Dawley rats were used in the study.…”
Section: Cell Culturementioning
confidence: 99%